2015
DOI: 10.1097/nmd.0000000000000353
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Contrasting Patterns for Suppression and Reappraisal Emotion Regulation Strategies in Alexithymia

Abstract: Alexithymia generally refers to difficulties in identifying and describing emotions. In this paper, two studies explored whether the emotion deficits observed in alexithymia may be related to the use of emotion regulation strategies. Relations with various sociodemographic variables were also explored. In the first study, 255 students completed the Emotion Regulation Questionnaire (ERQ) and the Toronto Alexithymia Scale-20. For the second study, 1107 participants from the general population completed the ERQ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 43 publications
5
23
1
8
Order By: Relevance
“…Consistent with expectations, individuals who report typically suppressing their emotions are more likely to report controlling their emotions and not expressing them to others and to have a greater difficulty in identifying and describing their emotions. These associations are consistent with other studies, eg, 1 study . Suppressors also tend to report lower emotional self‐efficacy, including concerns about difficulties communicating their emotions and staying focused on the present moment.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with expectations, individuals who report typically suppressing their emotions are more likely to report controlling their emotions and not expressing them to others and to have a greater difficulty in identifying and describing their emotions. These associations are consistent with other studies, eg, 1 study . Suppressors also tend to report lower emotional self‐efficacy, including concerns about difficulties communicating their emotions and staying focused on the present moment.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, individuals with high levels of alexithymia seem to use maladaptive emotion regulation strategies enhancing physiological aspects of emotional experience, suggesting that patients with SSD might also rely on dysfunctional emotion regulation styles (Laloyaux, Fantini, Lemaire, Luminet, & Laroi, ; Swart, Kortekaas, & Aleman, ). Traue () postulates that somatization is promoted by the suppression of negative feelings, which is in accordance with studies that have shown that suppression enhances physiological aspects of emotional experience (Alexander, ; Pennebaker & Seagal, ).…”
Section: Introductionmentioning
confidence: 99%
“…These restrict emotion awareness, resulting in subjective emotional experiences that do not correspond to physiological reactivity. Support for this interpretation comes mainly from correlational evidence of lower emotion regulation abilities, less use of adaptive strategies like reappraisal (Stasiewicz et al, 2012;Venta, Hart, & Sharp, 2012), and greater and more efficient use of repression, suppression (Laloyaux et al, 2015;Walker, O'Connor, & Schaefer, 2011), or experiential avoidance (Panayiotou et al, 2015) in alexithymia. Reliance on these strategies has been found to mediate alexithymia's association with problems like aggression (Velotti et al, 2016), depression, and psychosomatic symptomatology (Panayiotou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%